OCP Oracle Certified Professional Java SE 11 programmer I study guide : exam 1z0-815 - Boyarsky, Jeanne; Selikoff, Scott (Sybex, 2019)
The comprehensive study aide for those preparing for the new Oracle Certified Professional Java SE Programmer I Exam 1Z0-815 Used primarily in mobile and desktop application development, Java is a platform-independent, object-oriented programming language. It is the principal language used in Android application development as well as a popular language for client-side cloud applications. Oracle has updated its Java Programmer certification tracks for Oracle Certified Professional.' OCP Oracle Certified Professional Java SE 11 Programmer I Study Guide covers 100% of the exam objectives, ensuring that you are thoroughly prepared for this challenging certification exam. This comprehensive, in-depth study guide helps you develop the functional-programming knowledge required to pass the exam and earn certification. All vital topics are covered, including Java building blocks, operators and loops, String and StringBuilder, Array and ArrayList, and more.